Anionic ring opening polymerization of ε-caprolactone initiated by lithium silanolates - Satti, Angel Jose (2016)
Ring-opening homo- and co-polymerization reactions of ε-caprolactone were performed by employing anionic polymerization (high vacuum techniques) and lithium silanolates (LS) as initiators. LS were obtained by reaction between hexamethyl(cyclotrisiloxane) and sec-Bu–Li+, or from living poly(dimethylsiloxanyl)lithium chains. The results indicated that LS are efficient initiators for the ring-opening polymerization of ε-caprolactone, providing the respective homogeneous polymers in good yields.